Should drug testing be banned? - Millar, A. P. (Doping Journal, 2007)
Drug testing has been an abject failure in its aim of eliminating the use of performance enhancing substances in sport. Their use has continued and money has been wasted in fruitless efforts to improve the situation. Positive results have been excused by sporting bodies and athletes cleared on the flimsiest grounds. The only people penalised have been athletes when most of the decisions not to accept results have been by officials and they have not been penalised for breaking the rules. When advances in equipment can be used it is difficult to understand why chemical and pharmacological advances cannot be used. The arguments on the grounds of unfairness cannot be sustained and the dangers of drug use have been greatly exaggerated. Drug testing is controlled by WADA and there are many objections to its constitution. Until a more rational and honest approach is taken to the use of Performance Enhancing Substances, injustices will continue.